Combining ability analysis of earliness and yield of potato (Solanum tuberosum L.) genotype in Uganda - Namugga, Prossy; Sibiya, Julia; Melis, Rob; Barekye, Alex (Euphytica, 2018)
Potato (Solanum tuberosum L.) is a major food and cash crop mainly grown by small-scale farmers in the highland regions of Uganda. Changing global weather patterns require varieties that are able to grow within the short rainfall cycles and yield optimally under the prevailing conditions. The objectives of this study were to estimate the combining ability effects for early maturity, yield and yield related traits in potato. Eighteen F1 families generated from two sets of 12 parents using a North Carolina Design II were evaluated for days to 50% flowering, leaf senescence, yield and yield related traits in two different locations. Both additive and non-additive genetic effects influenced the expression of traits. However, additive genetic effects were predominant over the non-additive for most of the traits. The GCA/SCA ratios were 0.68 and 0.78 for days to 50% flowering and average tuber weight. Broad sense heritability estimates were 0.70 for total tuber weight and 0.78 for days to 50% flowering. The predominance of additive genetic effects implies that, genetic gains can be achieved through different selection methods and traits transferred to the respective progenies. Parents Rwangume, 396,038.107, 395,011.2, NKRK19.17, 393,077.54, Kimuri, and 392,657.8 had desirable GCA effects for the number of days to flowering and yield-related traits. Families of Rwangume × NKRK19.17, 393,077.54 × 395,011.2, 396,038.107 × Rwangume, and 396,038.107 × 395,011.2 had desirable SCA effects for yield and number of days to 50% flowering. The selected parents and families will be subjected to further clonal evaluation and selection.
Keywords: Combining Ability. Earliness. Gene action. Heritability. Maturity. Solanum tuberosum